COLORADO BEETLE (LEPTINOTARSA DECEMLINEATA) PEST OF POTATO - Erkinjon Khayitov; Inoyatullo Sulaymonov; Guzal Dustmurodova; Tolibjon Kosimov; Rikhsiniso Karimova (International Scientific and Current Research Conferences, 2021)
The main food plant is potatoes, but it can feed on eggplants, tomatoes and wild nightshade plants. Belongs to the order of beetles or beetles (Coleoptera), the family of leaf beetles (Chrysomelidae).